THU0503 Cost analysis of anti-osteoporotic drugs in real-world clinical practice. (12th June 2018) - Orlando, V.; Monetti, V.M.; Guerriero, F.; Russo, V.; Piscitelli, R.; Ruggeri, M.; menditto, E.
Abstract : Background: Nonadherence can reduce treatment effectiveness and can negatively affect healthcare costs and thus the treatments' cost-effectiveness. Adherence in the setting of osteoporosis has been shown to be just as problematic, if not worse, than that in other chronic diseases. Economic evaluations based on modelling are commonly used to compare alternative treatment strategies in osteoporosis, to support decision-makers and to inform treatment guidelines. Objectives: The aim of this study is to analyse healthcare costs of osteoporosis and to build a economic model cost-effectiveness of pharmacological intervents based on real world data. Methods: The data of the analysed subjects were drawn from the administrative databases of four Local Health Authorities in the Abruzzo Region. Patients 60 years of age or older were included if at least one prescription for any antiosteoporosis drugs had been filled in between January 1, 2006 and December 31, 2006. The patients were classified as exposed or not exposed to osteoporotic fracture. For each group, compliance with antiosteoporosis drugs was calculated. Patients were considered compliant if their Medication Possession Ratio (MPR) was ≥80%. The cost analysis was conducted taking each healthcare service into account, i.e. drug therapy, diagnostic tests and hospitalisation admissions, during the study period. A hypothetical scenario based on the real-life available evidence was constructed. The mean level of adherence to populate the hypothetical scenario of "full adherence" was set at MPR>80%. The model built by adding a step value, constrained by a normal random variable, to the real-word adherence of each subject so that the subject shifted to the hypotetical scenario of full adherence, in order to quantify the clinical outcome (number of fractures) achievable in the hypotetical scenario. Cost-effectiveness of full adherence compared to real world adherence was expressed in terms of Incremental Cost Effectiveness Ratio (ICER) and the number of fractures avoided was set as an effectiveness unit of measure. Results: The mean annual healthcare cost per fracture avoided was € 247.44, of which medical treatments and diagnostic tests accounted for € 103.60 (41.9%) and € 143.84 (58.1%), respectively. The mean annual helathcare cost per fractured patient was € 1, 044.85, of which medical treatments, diagnostic tests and hospitalizations for osteoporotic fracture accounted for € 88.73 (8.5%), € 169.48 (16.2%) and € 786.65 (75.3%), respectively. Conclusions: Costs per fractured patients resulted to be about four times greater than those of not fractured patients. Therefore, only enhancing adherence to medication may lead to reductions in the number of patients requiring hospitalisation. References: [1] Hiligsmann M, Boonen A, Rabenda V, Reginster JY. The importance of integrating medication adherence into pharmacoeconomic analyses: the example of osteoporosis2012;159–166. [2] Scotti L, Arfè A, Zambon A, Merlino L, Corrao G. Cost-effectiveness of enhancing adherence with oral bisphosphonates treatment in osteoporotic women: an empirical approach based on healthcare utilisation databases. BMJ open2014;4(3), e003758. Disclosure of Interest: None declared